Tobacco use, determinants and effects on treatment among persons living with HIV/AIDS at Military Hospital in Makurdi, Benue State, Nigeria - Aniwada, Elias C.; Ezema, Godian C.; Onwasigwe, Chika N. (International Journal Of Community Medicine And Public Health, 2022)
Background: Tobacco use is a leading avertable cause of premature death globally. It is commonly used among PLWHIV and with mortality tripling compared to the general population. Its impact on them is multifactorial. This study aims to assess the prevalence, determinants and effects of tobacco and its related products on treatment among persons living with HIV at a military hospital in Makurdi, Benue State, Nigeria Methods: The study was among HIV positive clients ≥18 years who have accessed care for ≥12 months at Nigerian air force hospital, Makurdi of Benue state, Nigeria. A descriptive cross-sectional study was done using adopted WHO ASSIST (V3.0) questionnaire. Simple random sampling method was used to select 700 clients studied. Results: About 138(19.7%) have used Tobacco products and 66 (9.4%) in past 3 months of which 10 (90.3%) were mild users. Of those that ever-used tobacco 114 (82.6%) used Tobacco and other substances; 90 (79.0%) Alcohol, 73 (64.0%) Kola nut, 8 (7.0%) Cannabis and 5 (4.4%) Cocaine. Determinants of use were male gender (AOR 0.23; 95% CI 0.15-0.35) and earning <18,000 (AOR 2.23; 95% CI 1.05-4.70). There were no associations of tobacco use with viral load and CD4 count. Conclusions: Prevalence of Tobacco use was higher than general population. Male gender and low socioeconomic status were determinants of use of tobacco. Addressing this menace of tobacco use is an important political and public health issue.